BEN JOHNSON AND HIS TRIBE, PECULIARITIES OF THEIR WORK AND ITS INFLUENCE ON THE LITERATURE - Kuatbaeva Sayatxan Maxmudovna,Scientific adviser: Khamitov Eldorbek E.,; Scientific adviser: Khamitov Eldorbek ErkinovichбNarxadjayeva Madina Abduvali qizi, (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
Ben Jonson, a prominent figure of the English Renaissance, and his literary circle significantly shaped early modern literature. His works, marked by classical forms, satirical wit, and moral rigor, reflect the peculiarities of the so-called “tribe” of poets and dramatists who valued structure, decorum, and intellectual precision. Jonson’s approach emphasized craftsmanship over inspiration, influencing contemporaries and successive generations of writers. The “tribe” collaborated in theatre, poetry, and literary criticism, promoting literary discourse and the codification of genres. Jonson’s comedies, masques, and lyric poems reveal a distinctive balance between social commentary and artistic discipline. His insistence on classical learning and civic engagement left an enduring mark on English literature, bridging Renaissance humanism and the evolving taste of the seventeenth century. This study explores the peculiarities of Jonson and his circle, highlighting their role in shaping literary standards and critical thought. Keywords: Ben Jonson, literary tribe, English Renaissance, satire, classical influence, literary craft, theatre, poetry.